PEMBERDAYAAN ANAK JALANAN DI KOTA CILEGON MELALUI PELATIHAN VOKASIONAL USAHA ON-LINE MENGGUNAKAN TEKNOLOGI INFORMASI KOMUNIKASI - Wardoyo, Siswo; Supriyanto, Supriyanto; Suhendar, Suhendar; Pramudyo, Anggoro Suryo (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
Street children (Anjal) become unsightly to be seen. They are victims of irregularities from irresponsible persons. Anjal still needs attention for his future. To improve the skills of Anjal, then on this program devotion is given vocational training internet-based, create email and an account at olx.co.id, offer goods on olx.co.id, delete items that have been sold in olx.co.id for business on-line through olx.Located at the Computer Laboratory of the Department of Electrical Engineering, Universitas Sultan Ageng Tirtayasa with a total of 12 participants attended from 20 invitations given, the training was conducted on Wednesday, July 27, 2016. The methods used were lecture, practice, question and answer, discussion and practice.Based on the results of evaluations conducted in general there is an increase in the knowledge of trainees of Anjal empowerment through web design training for on-line business. The increase indicator that participants who have e-mail increased 67% from 4 people to 12 people. Participants understanding on-line sales increased 59% from 2 to 9. Participants who already have a business on-line sales increased 58% from 1 person to 8 people. The expected end result Anjal income, self-adolescent, well-established and anjal can be an exemplary example for the other childhood.